The important role of routine cytopathology in pediatric precision oncology. Issue 10 (27th May 2021) - Xie, Jinhan; Kumar, Amit; Dolman, M. Emmy M.; Mayoh, Chelsea; Khuong‐Quang, Dong‐Anh; Cadiz, Roxanne; Wong‐Erasmus, Marie; Mould, Emily V. A.; Grebert‐Wade, Dylan; Barahona, Paulette; Kamili, Alvin; Tsoli, Maria; et al.
Abstract : Background: The development of high‐throughput drug screening (HTS) using primary cultures provides a promising, clinically translatable approach to tailoring treatment strategies for patients with cancer. However, this has been challenging for solid tumors because of often limited amounts of tissue available. In most cases, in vitro expansion is required before HTS, which may lead to overgrowth and contamination by non‐neoplastic cells. Methods: In this study, hematoxylin and eosin staining and immunohistochemical staining were performed on 129 cytopathology cases from 95 patients. These cytopathology cases comprised cell block preparations derived from primary tumor specimens or patient‐derived xenografts as part of a pediatric precision oncology trial. Cytopathology cases were compared with the morphology and immunohistochemical staining profile of the original tumor. Cases were reported as tumor cells present, equivocal, or tumor cells absent . The HTS results from cytopathologically validated cultures were incorporated into a multidisciplinary tumor board report issued to the treating clinician to guide clinical decision making. Results: On cytopathologic examination, tumor cells were present in 77 of 129 cases (60%) and were absent in 38 of 129 cases (29%), whereas 14 of 129 cases (11%) were equivocal. Cultures that contained tumor cells resembled the tumors from which they were derived. Conclusions: Cytopathologic examination of tumor cell block preparations is feasible and provides detailed morphologic characterization. Cytopathologic examination is essential for ensuring that samples submitted for HTS contain representative tumor cells and that in vitro drug sensitivity data are clinically translatable. Abstract : Routine cytopathology is able to establish the presence or absence of tumor cells in primary cultures derived from patients with pediatric cancer. Cytopathologic examination ensures the clinical relevance of in vitro drug sensitivity profiling in a pediatric precision oncology platform.